Synthesis, characterization, and polymerization of a novel benzoxazine based on diethyltoluenediamine. Issue 17 (16th January 2015) - Ren, Shitong; Yang, Xin; Zhao, Xiaojuan; Zhang, Ying; Huang, Wei
ABSTRACT: A novel aromatic diamine‐based benzoxazine monomer (PDETDA) was successfully prepared from diethyltoluenediamine (DETDA), phenol, and paraformaldehyde through a simple one‐step solvent‐less method. The structure of PDETDA was confirmed by FTIR, 1 H NMR, and 13 C NMR. The curing behavior of PDETDA was studied by DSC, FTIR, and rheological measurement. The results showed that the alkyl substituents on the benzene ring in DETDA not only facilitated the synthesis of PDETDA by effectively hindering the formation of triazine network, but also endowed PDETDA with the advantage of low viscosity (1 Pa s at 90°C). However, steric hindrance of the substituents made PDETDA difficult to form a crosslinked network through ring‐opening polymerization, and therefore only oligomers and noncrosslinked polymers were obtained. The curing kinetics of PDETDA was studied by nonisothermal DSC, and the results revealed that the curing of PDETDA displayed autocatalytic characteristic. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2015, 132, 41920. Abstract :